PTU-133 Ready to go and let go: perspectives on transition and transfer from paediatric to adult health care: a paired pilot survey of adolescent IBD patients and their parents. (28th May 2012) - Rao, N; Ashok, D; Azaz, A; Sebastian, S
Abstract : Introduction: National surveys report that transition care in inflammatory Bowel Disease is still not well developed. Although the general principles guiding transition of adolescents with chronic illnesses from paediatric to adult health care have been established, there are no studies to assess the transfer needs and concerns of adolescents with IBD and their carers. We aimed to gauge the perspectives of adolescents with IBD and their parents to determine their issues, concerns and expectations. Methods: A cross sectional survey of IBD patients starting transition process in a dedicated transition clinic and their parents was undertaken using a semi-structured questionnaire designed for self completion. Along with demographic and clinical information, respondents were asked to rate on a scale of 1–5 (using Likert scale anchored by 1-least important and 5-very important and essential) their responses on their perceived importance on the aspects of preparation, self management skills, concerns regarding transfer and value of support services. Results: 20 patients (12 Crohn's and 8 Ulcerative Colitis) and their parents completed the survey independently. There was concordance in the responses of patients and their parents in rating highly the need for information, education and co-ordination of transfer process (Abstract PTU-133 table 1). The knowledge, empathy and accessibility were identified as key attributes for the transferring adult team (Abstract PTU-133 table 2). The highest rated concern for both adolescents and their parents was the perceived differences in performing tests such as endoscopy (mean score of 4.55±0.17 and 4.65±0.23 respectively). The adolescents favoured to attend appointments without parents before transfer (mean score 3.65±1.18) as opposed to their parents (mean score 1.9±1.16). In addition parents were concerned whether they will become less involved in care following transfer (mean score 4.15. The adolescents' favoured younger age of transition and transfer when compared to their parents. While dedicated adolescent services were described as beneficial by patients and their parents, only 50% of patients preferred to have joint appointments. Conclusion: This first pilot study demonstrates significant concerns about transition process needing addressing among adolescent IBD patients and their parents. Patients and parents differ in their rating of independence and self advocacy needed at the time of transfer. Tailoring transition to individual patient and parent needs without dedicated transition care teams may be challenging. Competing interests: None declared.